STRATEGIC AND PERSONNEL APPROACH TO THE GROWTH OF THE GAS INDUSTRY - Borisovna Baurina, Svetlana; Petrovich Garnov, Andrey; Alexandrovna Chaikovskaya, Lyubov; Yurievna Garnova, Victoria; Nicolaevna Bykova , Olga (Revista Inclusiones, 2019)
The paper discusses how to apply strategic and personnel approaches to the growing gas industry. Here we describe the strategic philosophy that will help preserve the business, regardless of market volatility in the short term. The key challenge of the gassector is, of course, its inherent volatility. The producers will need time to take into account unpredictability in terms of excess supply or unmet market demand. In addition, they will have to overcome the difficulties associated with the pace and scaleof the transition to generating power from non-fossil sources. Given these uncertainties, gas companies need to develop a viable strategy to mitigate these risks.